PENGARUH HARGA TERHADAP VOLUME PENJUALAN PUPUK UREA BERSUBSIDI PADA PT. PERTANI (PERSERO) CABANG BANTEN - Miftah Faiz Ali Ramdhani; Yulianti Rahmat (P3M Politeknik Negeri Banjarmasin, 2023)
This study aims to determine the effect of price on sales volume of subsidized urea fertilizer at PT. Pertani (Persero) Banten Branch. The formulation of the problem in this study is how the price of subsidized urea fertilizer affects PT. Pertani (Persero) Banten Branch, how the sales volume of subsidized urea fertilizer is at PT. Pertani (Persero) Banten Branch, and how much influence the price has on the sales volume of subsidized urea fertilizer at PT. Pertani (Persero) Banten Branch Branch, and how much influence the price has on the sales volume of subsidized urea fertilizer at PT. Pertani (Persero) Banten Branch. The research method used is a quantitative approach with an associative type. Then in this study using purposive sampling technique. The type of data used is secondary data. The results showed that the price variable had a significant effect on sales volume. Based on the results of the t test, the t count is -6.348 and the t table value is 1.71387. thuis the value of t count is greater than t table (-6.348>1.71387), the Ho is rejected and Ha is accepted. It is concluded that the price variable is negative.